DNA damage accumulation and TRF2 degradation in atypical Werner syndrome fibroblasts with LMNA mutations - Saha, Bidisha; Zitnik, Galynn; Johnson, Simon C.; Nguyen, Quyen; Risques, Rosa Ana; Martin, George M.; Oshima, Junko (Frontiers in Genetics, 2013)
Segmental progeroid syndromes are groups of disorders with multiple features suggestive of accelerated aging. One subset of adult-onset progeroid syndromes, referred to as atypical Werner syndrome, is caused by mutations in the LMNA gene, which encodes a class of nuclear intermediate filaments, lamin A/C. We previously described rapid telomere attrition and accelerated replicative senescence in cultured fibroblasts overexpressing mutant lamin A. In this study, we investigated the cellular phenotypes associated with accelerated telomere shortening in LMNA mutant primary fibroblasts. In early passage primary fibroblasts with R133L or L140R LMNA mutations, shelterin protein components were already reduced while cells still retained telomere lengths comparable to those of controls. There was a significant inverse correlation between the degree of abnormal nuclear morphology and the level of TRF2, a shelterin subunit, suggesting a potential causal relationship. Stabilization of the telomeres via the introduction of the catalytic subunit of human telomerase, hTERT (human telomerase reverse transcriptase), did not prevent degradation of shelterin components, indicating that reduced TRF2 in LMNA mutants is not mediated by short telomeres. Interestingly, γ-H2AX foci (reflecting double strand DNA damage) in early passage LMNA mutant primary fibroblasts and LMNA mutant hTERT fibroblasts were markedly increased in non-telomeric regions of DNA. Our results raise the possibility that mutant lamin A/C causes global genomic instability with accumulation of non-telomeric DNA damage as an early event, followed by TRF2 degradation and telomere shortening.